Localization and characterization of val‐opsin isoform‐expressing cells in the brain of adult zebrafish. Issue 17 (11th August 2014) - Hang, Chong Yee; Kitahashi, Takashi; Parhar, Ishwar S.
ABSTRACT In addition to vision, light information is used to regulate a range of animal physiology. Such nonimage‐forming functions of light are mediated by nonvisual photoreceptors expressed in distinct neurons in the retina and the brain in most vertebrates. A nonvisual photoreceptor vertebrate ancient long opsin (VAL‐opsin) possesses two functional isoforms in the zebrafish, encoded by valopa and valopb, which has received little attention. To delineate the neurochemical identities of valop cells and to test for colocalization of the valop isoforms, we used in situ hybridization to characterize the expression of the valop genes along with that of neurotransmitters and a neuropeptide known to be present at the sites of valop expression. Double labeling showed that the thalamic valop population coexpresses valopa and valopb. All the thalamic valop cells overlapped with a GABAergic cell mass that continues from the anterior nucleus to the intercalated thalamic nucleus. A novel valopa cell population found in the superior raphe was serotonergic in nature. A valopb cell population in the Edinger‐Westphal nucleus was identified as containing thyrotropin‐releasing hormone. Valopb cells localized in the hindbrain intermediate reticular formation were noncholinergic in nature (nonmotorneurons). Thus, the presence of valop cell populations in different brain regions with coexpression of neurotransmitters and neuropeptides and the colocalization of valop isoforms in the thalamic cell population indicate regulatory and functional complexity of VAL‐opsin in the brain of the zebrafish. J. Comp. Neurol. 522:3847–3860, 2014. © 2014 Wiley Periodicals, Inc.